Teologia şi structura ei educaţională - Șanta, Gheorghe (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2019)
Theology helps us to clarify our spiritual states and discovers our great ideals of faith and living, it discovers that a vocation, or a call from God, can suddenly, volcanically, or in a slow form, appear as a the fulfillment of a day whose thunderstorms and blackness gradu- ally dissipate, so that the sun shines brightly, illuminating everything, warming everything from the azure of the sky. The service of truth is the service of God, and the theologian must be a witness of the truth. Therefore, he who prepares to be such a wit- ness of the truth must strive to identify himself with this mission, liv- ing in what he says. Theology means prayer, contemplation, asceticism, study, liturgical experience, knowledge of man and the world. it is not possible to sep- arate theology from spirituality, because dogma is not an intellectual scheme, or a combination of theoretical notions, but a spiritual real- ity, which must be lived personally.